What to do with negative and positive HPV test to cytology? About a case - Jeronimo, Jose (2016)
Prevention of cervical cancer has evolved very rapidly in recent years; now has a better understanding of the natural history of infection with oncogenic human papilloma virus, is known more about the genesis of pre-cancerous lesions and subsequent progression to invasive cancer (1). As a result of this better understanding of the natural history of disease, it has also seen an evolution in the recommendations for detection (2) and management of precursor lesions of cervical cancer (3). In this issue we are presenting the first case for discussion, which must be followed by other cases shared by the author, or cases received from colleagues readers of this magazine.